Invasive- versus computed tomography-angiography for the evaluation of coronary artery disease among elderly patients undergoing transcatheter aortic valve implantation. (25th November 2020) - Berkovitch, A; Finkelstein, A; Barbash, I.M; Fefer, P; Maor, E; Banai, S; Brodov, Y; Goitein, O; Aviram, G; Halkin, A; Guetta, V; Steinvil, A; et al.
Abstract: Background: Coronary artery disease (CAD) is common among elderly patients with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI). Current guidelines recommend that percutaneous coronary intervention (PCI) of >70% proximal coronary lesions prior to TAVI. The aim of the current study was to evaluate two approaches to CAD diagnosis pre-TAVI. Methods: We investigated 2, 027 patients undergoing TAVI for severe aortic stenosis at two large centers with different pre-procedural CAD assessment: pre-TAVI computed tomography angiography (CTA) with selective invasive angiography according to CTA results (N=831) or mandatory invasive angiography (IA) (N=1, 196). Peri-procedural complications were documented according to the VARC-2 criteria. Mortality rates were prospectively documented. Results: Mean age of the study population was 86±4, of whom 55% were female. Patients in the IA group had significantly higher rates of pre-TAVI PCI compared to the CTA group (32% vs. 17%, p<0.001). Following TAVI, peri-procedural myocardial infarction (MI) rates were significantly lower among the IA group (0.1% vs. 1.5%, p=0.001). However, multivariate binary logistic regression analysis adjusted for age, gender and cardiovascular risk factors failed to show association between centers strategy and peri-procedural MI. Periprocedural bleeding rates were similar between the groups (3.5% vs. 2.9%, p=0.477). Thirty day, and 1-year mortality crude rates were similar between the groups (2.5% vs. 3.4%, p=0.25, and 10.2% vs. 12.0%, p=0.19). Multivariate cox regression adjusted for age, gender and cardiovascular risk factors did not find association between CAD clearance strategy and outcome. Conclusions: In elderly patients, CTA driven approach for CAD evaluation pre-TAVI is a valid strategy with similar outcome as compared to invasive approach. CTA strategy significantly reduces invasive procedures rates without compromising patient's outcome. Funding Acknowledgement: Type of funding source: None